Pediatric multiple sclerosis: update on diagnostic criteria, imaging, histopathology and treatment choices - Chou, I-Jun; Wang, Huei-Shyong; Whitehouse, William P.; Constantinescu, Cris S. (Springer, 2016)
Pediatric multiple sclerosis (MS) represents less than 5% of the MS population, but patients with pediatric-onset disease reach permanent disability at a younger age than adult onset patients. Accurate diagnosis at presentation and optimal long-term treatment is vital to mitigate ongoing neuroinflammation and irreversible neurodegeneration. However, it may be difficult to early differentiate pediatric MS from acute disseminated encephalomyelitis (ADEM) and neuromyelitis optica spectrum disorders (NMOSD) as they often have atypical presentation that differs from that of adult-onset MS. The purpose of this review is to summarize the updated views on diagnostic criteria, imaging, histopathology and treatment choices.